Peran Pentahelix melalui Focus Group Discussion (FGD) dalam Pengembangan Desa Wisata Bawomataluo Kecamatan Fanayama Kabupaten Nias Selatan - Trinitas Harefa; Apriliana Lase; Erika Christine Panggabean; Ade Putera Arif Panjaitan; Rusmauli Simbolon (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of Pentahelix elements in the development of Bawomataluo Tourism Village, Fanayama District, South Nias Regency, and identify supporting and inhibiting factors in its implementation through Focus Group Discussions (FGDs). The method used is descriptive qualitative with a case study approach, through observation techniques, in-depth interviews, FGDs, and documentation. The FGD was held on May 17, 2026, at the Bawomataluo Village Hall, involving five speakers from the Government, Academics, Business Actors, Community, and Media (ABCGM). Data analysis used the interactive model of Miles, Huberman, and Saldana, reinforced by Freeman's Stakeholder Theory. The results show that the government plays a role as a regulator, academics as conceptors, business actors as drivers of the creative economy, the community as cultural preservers, and the media as a means of digital promotion. Supporting factors include cultural richness (Hombo Batu, Omo Hada, Gowe Statue), ADWI 2022 recognition, and UNESCO Tentative List status. Inhibiting factors include suboptimal coordination between elements, limited local human resources, and inconsistent social media management. The structured synergy of all Pentahelix elements is key to the successful development of this tourism village.